Enhancing market power by reducing switching costs - Jan Bouckaert; Hans Degryse; Thomas Provoost (Center for Economic Studies and ifo Institute (CESifo), 2008)
Competing firms often have the possibility to jointly determine the magnitude of consumers' switching costs. Examples include compatibility decisions and the option of introducing number portability in telecom and banking. We put forward a model where firms jointly decide to reduce switching costs before competing in prices during two periods. We demonstrate that the outcome hinges crucially on how the joint action reduces consumers' switching costs. In particular, firms will enhance their market power if they implement measures that reduce consumers' switching costs by a lump sum. Conversely, they will preserve market power by not implementing actions that reduce switching costs proportionally. Hence, when policy makers design consumer protection policies, they should not always adopt a favourable attitude towards efforts by firms to reduce switching costs.
Keywords: D43; 330; Switching costs; market power; welfare; Wechselkosten; Marktmacht; Preiswettbewerb; Theorie